Primer registro del copépodo de aguadulce Mesocyclops paranaensis Dussart& Frutos, 1986 (Copepoda: Cyclopoida: Cyclopidae) de Colombia - Fuentes-Reinés, Juan M. (2021)
The Neotropical free-living freshwater cyclopoid copepod Mesocyclops paranaensis Dussart & Frutos, 1986 was found in a small temporal pond in La Guajira, northern Colombia. Hitherto, it has been reported from Argentina, Paraguay, and Brazil. This is the first record of this species in Colombia, its northernmost finding in South America, and the fourth locality in which this species has been recorded from. Mesocyclops paranaensis can be distinguished from its closest congeners by a unique combination of the characters of the female, including: 1) leg 4 intercoxal sclerite with two large, acute projections; 2) P3, P4 intercoxal sclerite caudal surface lightly pilose; 3) seminal receptacle with narrow lateral arms and weakly convex anterior margin; 4) second antennary endopodite with seven setae, and insertion of antennary exopodal seta with adjacent spinules; 5)frontal surface of P1 basipodite ornamented with long spinules; 6) posterior margin of anal somite with continuous row of spinules; and 7) inner margin of caudal ramus hirsute. The Colombian population shows some subtle morphological differences with respect to previous reports.